Urinary Tract Infections in Children. Approaches to Etiotropic Therapy - O.Ye. Chernyshova; S.Ya. Yaroshenko (Zaslavsky O.Yu., 2014)
The paper presents approaches to rational antibiotic treatment of urinary tract infections in children with a choice of effective and safe antimicrobial agents - indications for their use and methods of application.